1986
DOI: 10.1172/jci112618
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness is a major determinant of femoral neck and lumbar spine bone mineral density.

Abstract: The relationship between physical fitness and bone mass in the femoral neck, lumbar spine, and forearm was studied in 84 normal women. Femoral neck and lumbar spine bone mineral density and forearm bone mineral content were estimated by absorptiometry. Fitness was quantitated from predicted maximal oxygen uptake. Femoral neck and lumbar bone mineral density were significantly correlated with fitness as well as age and weight.in the 46 postmenopausal'subjects, fitness was the only significant predictor of femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(54 citation statements)
references
References 34 publications
5
47
1
1
Order By: Relevance
“…Our MEM weighed more than the runners, but normalizing BMD for weight did not materially alter this result. In contrast to Pocock et al (35), we found no significant relationship between physical fitness, defined by VO 2 max., and bone density. We have previously shown that highimpact weight-bearing activity, such as gymnastics, may provide loading forces powerful enough to stimulate osteogenesis (36).…”
Section: Journal Of Endocrinology (1998) 138contrasting
confidence: 99%
“…Our MEM weighed more than the runners, but normalizing BMD for weight did not materially alter this result. In contrast to Pocock et al (35), we found no significant relationship between physical fitness, defined by VO 2 max., and bone density. We have previously shown that highimpact weight-bearing activity, such as gymnastics, may provide loading forces powerful enough to stimulate osteogenesis (36).…”
Section: Journal Of Endocrinology (1998) 138contrasting
confidence: 99%
“…McVeigh et al 32) observed an inverse response relationship between less activity, filled in questionnaire self-reporting method, and the likelihood of mineralization in rheumatoid arthritis. The present data agree with previous findings that less physical activity, as well as low fitness, are related to bone metabolic disease including osteopenia and osteoporosis 21,24) . However, this study had several limitations.…”
Section: Discussionsupporting
confidence: 93%
“…Low grip strength has usually been less strongly associated with the risk of bone metabolic diseases compared to higher strength 20) . A number of studies of hand grip strength and BMD have been performed long ago, and the test was used to measure physiologic function in the elderly 4,[20][21][22] . The results of the present study, indicating a link between low grip strength and increased prevalence of osteopenia, might lead to changes in the decreasing BMD in middle-aged men.…”
Section: Discussionmentioning
confidence: 99%
“…For a patient with the average (mean) femoral BMD, a variation in physical activity within the normal range seen in the present study (i.e., mean t_ 2 SD) could account for an 18.5% variation in the observed BMD. This is consistent with our recent finding that physical fitness, measured as predicted maximum oxygen uptake, is an important determinant of femoral neck BMD in normal women (21). Loss of function associated with joint involvement precludes the use of such objective methods of assessing physical fitness and activity in RA patients.…”
Section: Discussionsupporting
confidence: 91%